Push Notification Pada Sistem Penjualan Tiket Workshop dan Event Menggunakan Firebase Cloud Messaging Berbasis Progressive Web Application - Nirwan Jaya Suwarno; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2021)
The use of website technology in the ticket sales system is the rightstep to improve the company's business processes. The use of thewebsite can have a great impact on the buyers and sellers of tickets,namely with the existence of a website information will be easilyaccessible. However, after successfully carrying out the process ofbuying and selling tickets through the website, the seller needs quitea lot of time or has not been effective in communicating with thebuyers. This problem occurs because buyers use variouscommunication, so the sellers need to use sundry applications toreach all buyers.This ineffective way of communicating can be solved by embeddinga feature on the website, namely push notifications. Seller can usepush notifications to send broadcast messages to their buyerswithout missing anything. All buyers can be reached easily becausepush notifications are embedded directly in the application so thatbuyers do not need to install other applications to communicatewith sellers.The results showed that the ticket sales system with pushnotifications succeeded in increasing the effectiveness decrease thetime of using the application to send messages by 38.4% comparedto using external applications.